Robust Two-Way Cognitive Relaying: Precoder Designs under Interference Constraints and Imperfect CSI - Ubaidulla, P.; Aissa, Sonia (IEEE transactions on wireless communications, 2014)
We present various robust precoder designs for two-way relaying in a cognitive radio network, where a pair of cognitive (or secondary) transceiver nodes communicate with each other assisted by a set of cognitive two-way relays. The secondary nodes share the spectrum with a licensed primary user (PU) node while keeping the interference to the PU below a specified threshold. The PU node and the cognitive transceivers employ single transmit/receive antennas whereas the secondary relay nodes employ multiple transmit/receive antennas. The proposed precoder designs ensure robust performance in the presence of errors in the channel state information (CSI). Such robust designs are of significant interest since in practice it is very difficult to obtain perfect CSI. We consider CSI errors with two different types of characterization and corresponding robust designs. First, we consider robust relay precoder designs that are applicable when CSI errors have known first and second moments. Next, we consider robust designs that are applicable when the CSI error can be characterized in terms of spherical uncertainty region. We show that the proposed designs can be reformulated as convex optimization problems that can be solved efficiently. Through numerical simulations and comparisons we illustrate the performance of the proposed designs.